Kontroversi Kebijakan Pengelolaan Kawasan Pariwisata Alam: Studi Kasus UU Konservasi Sumber Daya Alam dan Ekosistem di Sektor Pariwisata Indonesia - Ibna Suwita, Dyah Arrum (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research is to see what controversies arise in the implementation of the Natural Resources and Ecosystem Conservation Law in the tourism sector, especially related to conflicts of interest between natural area managers, local and tourism industry parties as well as the impact of implementing the Natural Resources and Ecosystem Conservation Law on the management of natural tourist areas in Indonesia, especially in balancing the economic interests of tourism and environmental conservation. This research method uses two main approaches, namely literature analysis research and SWOT, to dig deeper into policies for managing natural tourist areas in Indonesia and their impact on ecosystems and the tourism sector. The research results show that natural area managers often face a dilemma between preserving the ecosystem and attracting investment in the tourism sector which can provide economic benefits. Local communities who depend on natural resources sometimes feel marginalized by overly strict management policies, while the tourism industry often urges looser policies to facilitate investment and infrastructure development.